Metabolomic Analysis Reveals That the Drosophila melanogaster Gene lysine Influences Diverse Aspects of Metabolism. - St Clair, S.L.; Li, H.; Ashraf, U.; Karty, J.A.; Tennessen, J.M. (Genetics, 2017)
The fruit fly Drosophila melanogaster has emerged as a powerful model for investigating the molecular mechanisms that regulate animal metabolism. However, a major limitation of these studies is that many metabolic assays are tedious, dedicated to analyzing a single molecule, and rely on indirect measurements. As a result, Drosophila geneticists commonly use candidate gene approaches, which, while important, bias studies toward known metabolic regulators. In an effort to expand the scope of Drosophila metabolic studies, we used the classic mutant lysine (lys) to demonstrate how a modern metabolomics approach can be used to conduct forward genetic studies. Using an inexpensive and well-established gas chromatography-mass spectrometry-based method, we genetically mapped and molecularly characterized lys by using free lysine levels as a phenotypic readout. Our efforts revealed that lys encodes the Drosophila homolog of Lysine Ketoglutarate Reductase/Saccharopine Dehydrogenase, which is required for the enzymatic degradation of lysine. Furthermore, this approach also allowed us to simultaneously survey a large swathe of intermediate metabolism, thus demonstrating that Drosophila lysine catabolism is complex and capable of influencing seemingly unrelated metabolic pathways. Overall, our study highlights how a combination of Drosophila forward genetics and metabolomics can be used for unbiased studies of animal metabolism, and demonstrates that a single enzymatic step is intricately connected to diverse aspects of metabolism.